'It's complicated': Professional opacity, duality, and ambiguity—A response to Noordegraaf (2020). Issue 2 (5th July 2021) - Alvehus, Johan; Avnoon, Netta; Oliver, Amalya L
Abstract: In this comment to Noordegraaf's 'Protective or connective professionalism? How connected professionals can (still) act as autonomous and authoritative experts', we argue that Noordegraaf has contributed significant insights into the development of contemporary professionalism. However, we argue for a less binary and more complex view of forms of professionalism, and for finding ways of understanding professionalism grounded in a relational view of everyday professional work. The first section (by Johan Alvehus) suggests that Noordegraaf's 'connective professionalism' is primarily about new ways of strengthening professionalism's protective shields by maintaining functional ambiguity and transparent opacity around professional jurisdictions. The second section (by Amalya Oliver and Netta Avnoon) argues for viewing professionalism on a range of protection–connection and offers an approach for understanding how connective and protective models co-occur. Both commentaries thus take a relational, dynamic, and somewhat skeptical view on the reproduction and maintenance of professionalism.